Blunted Muscle Mitochondrial Responses to Exercise Training in Older Adults With HIV. (30th December 2020) - Jankowski, Catherine M; Wilson, Melissa P; MaWhinney, Samantha; Reusch, Jane; Knaub, Leslie; Hull, Sara; Erlandson, Kristine M
Abstract: Background: Muscle mitochondrial dysfunction associated with HIV and antiretroviral therapy (ART) may improve with exercise. Methods: Muscle specimens obtained before and after 24 weeks of exercise in older people with HIV (PWH; n = 18; ART >2 years) and uninfected controls (n = 21) were analyzed for citrate synthase (CS) activity and complexes (C) I–V, manganese superoxide dismutase (MnSOD), peroxisome proliferator-activated receptor-γ coactivator-1 (PGC1α), and voltage-dependent anion channel 1 (VDAC1) content. Results: Only controls had increased CS, MnSOD, PGC1α, and CIV ( P ≤ .01; P < .01 vs PWH) after training. Conclusions: The blunted mitochondrial adaptations to training in PWH suggests the need for different types of exercise-induced stimulation. Clinical Trials Registration: NCT02404792.